Oxidative stress and changes in adenosine deaminase activity of cattle experimentally infected by Fasciola hepatica - Da Silva A.S.* (2017)
© 2016 Cambridge University Press.The aim of this study was to evaluate the oxidative stress in serum and liver and adenosine deaminase (ADA) activity of cattle experimentally infected by Fasciola hepatica. The group A consisted of five healthy animals (uninfected), and the group B was composed of five animals orally infected with 200 metacercariae of F. hepatica. On days 20, 40, 60 and 80 post-infection (PI) serum was collected to measure oxidative stress variables. On day 100 PI, animals were humanely euthanized and liver samples were collected. Infected animals showed lower (P < 0·05) seric ADA activities on days 40 and 60 PI but higher (P < 0·05) in the liver tissue compared with uninfected animals. Seric and hepatic reactive oxygen species (ROS) were higher (P < 0·05) in infected compared with uninfected animals. Hepatic thiobarbituric acid reactive substances were higher (P < 0·05) in infected animals. Catalase and glutathione S-transferase activities were lower in liver tissue of infected animals, while glutathione peroxidase was higher compared with uninfected (P < 0·05). In summary, we conclude that oxidative stress occurs in cattle experimentally infected by F. hepatica, mainly due to excessive ROS production in the course of fasciolosis, contributing to hepatic damage, and that increased in hepatic ADA activity may contribute to the inflammatory process.